Testing the interest parity condition with Irving Fisher's example of Indian rupee and sterling bonds in the London financial market (1869-1906) - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2017)
This paper assesses the uncovered interest parity (UIP) condition by means of Indian government bonds during the 1869 to 1906 period. As emphasised by Irving Fisher, interest and exchange rates between Britain and India from that period concur closely with the theoretical assumptions of UIP since (i.) India issued bonds in different currencies (rupees and sterling) (ii.) these bonds were simultaneously traded in the London financial market, and (iii.) subject to negligible regulation and default risks. As long as the Indian currency system was stable, a close correlation arises indeed between sterling-to-rupee interest rate differences and exchange rate changes.
Keywords: F31; N13; N23; 330; India; Irving Fisher; Silver currency; Uncovered Interest Parity; UIP Puzzle